Development of a real time PCR-based method for the detection of the two spotted cricket Gryllus bimaculatus in food - Hauke Fehrs (2023)
During the past decades insects have attracted much attention as an alternative food source. High nutritional value and a small carbon food print, as well as the ability of easily being farmed in a high scale potentially make them one of the solutions to the challenges posed by a rapidly growing population. Even in western societies, where “entomophagy”, the eating of insects, does not have much tradition and is mostly refused, more and more insect derived foods are entering the market. Such as for other novel foods, edible insects come with risks for the consumer, due to the potential presence of chemical and biological hazards and the possibility of allergic reactions. The two spotted cricket Gryllus bimaculatus is a species not permitted in food or feedstuff for livestock, but it is anyway farmed as food for pets and as fish bait. Its presence on the market could derive into a misuse of this insect and of its products thereof, potentially leading to a food fraud. Furthermore, contaminations between allowed and prohibited species could occur in farms where different kinds of crickets are kept. Hence, a reliable method for the detection of the species not yet allowed is needed to ensure consumers safety, which was the aim of this bachelor thesis. For the development of the system a real time PCR-based approach was chosen. After in-silico analyses for the detection of the most suitable target genes, several sets of primers were ordered and tested using endpoint PCR followed by gel electrophoresis. Afterwards, the primers were tested in a real time PCR assay employing SYBR® green, and for the best performing set a TaqMan™ probe was developed. Several DNA samples isolated from different species were tested to ensure specificity, among which insects, crustaceans, mollusks, fishes, land animals and plants. Additionally, sensitivity and efficiency of the method were determined, and the limit of detection was derived. Finally, the practical applicability was verified on a small selection of foods. The system generally produced satisfying results, but further experiments must be made to complete the validation.